Leadership Decision-Making Styles and Managerial Practices in Organizational Excellence from the Case of Ramayana - S Chandramouli, Mr.; C.Madhavi, Dr. (International Journal of Engineering and Technology, 2018)
Wealth and happiness of a nation depends on the efficiency and effectiveness of the economic activities of the economic units of all sizes and microeconomic objectives. Scholars from the West and the East have long suggested ways to improve the efficiency and effectiveness of an organization. It is unanimously agreed by all scholars that leadership of the organization plays a critical role besides better management practices in determining the efficiency of all the human resources and thereby the other resources and ultimately that of the whole organization. Also it has been widely believed in India that works such as the Mahabharata and Ramayanaa, as a single big case themselves, deals with many problems of various types and prescribes guidelines thereof. It is also generally believed that the case method of teaching and learning was pioneered by the Harvard Law School and popularized by the Harvard Business School. However it is common knowledge in India that Ramayanaa and Mahabharata, Panchatantra, etc has pioneered the case method of teaching and learning thousands of years before the recent rediscovery of the case method. This paper attempts to analyze only a part or module of the case of Ramayanaa for its varied implications (including legal issues, succession issues, conflicts, manipulation by the top-management, etc.) prescribing leaders and managers for their organizational excellence inÂ the modern times. These implications seem to be not only consistent with the modern concepts but also very relevant even today!Â Â